A new hypothesis for the origin of Amazonian Dark Earths - Lucas C. R. Silva (Nature Portfolio, 2021)
Amazonian Dark Earth is soil that has had mysteriously high fertility since ancient times, despite the fact that surrounding soils have very low nutrients. Here the authors’ use of isotope reconstructions indicate that these soils predate human settlement and could have alluvial and burning origins.